2020
DOI: 10.1126/sciadv.aax5979
|View full text |Cite
|
Sign up to set email alerts
|

Efficient inverse graphics in biological face processing

Abstract: Vision not only detects and recognizes objects, but performs rich inferences about the underlying scene structure that causes the patterns of light we see. Inverting generative models, or “analysis-by-synthesis”, presents a possible solution, but its mechanistic implementations have typically been too slow for online perception, and their mapping to neural circuits remains unclear. Here we present a neurally plausible efficient inverse graphics model and test it in the domain of face recognition. The model is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 58 publications
1
72
0
Order By: Relevance
“…Here, we sought to overcome these limitations by adopting the underlying theoretical idea (wiring cost minimization), but building upon recent advances in ANN models (1,12,36). Notably, that prior deep ANN modeling work has already qualitatively demonstrated the presence of at least some "face neurons" within model IT (36) and more recent studies have demonstrated the existence of face-selective units in deep ANNs (37)(38)(39). However, the correspondence of face processing in ANNs and the primate ventral stream has not been tested systematically.…”
Section: Category Choicementioning
confidence: 99%
“…Here, we sought to overcome these limitations by adopting the underlying theoretical idea (wiring cost minimization), but building upon recent advances in ANN models (1,12,36). Notably, that prior deep ANN modeling work has already qualitatively demonstrated the presence of at least some "face neurons" within model IT (36) and more recent studies have demonstrated the existence of face-selective units in deep ANNs (37)(38)(39). However, the correspondence of face processing in ANNs and the primate ventral stream has not been tested systematically.…”
Section: Category Choicementioning
confidence: 99%
“…Explicit experimental hypotheses are directly tied to the parameterisation of stimuli by generative models and vice versa. For example, we explicitly tested that a parameterisation of faces in terms of their 3D shape and RGB texture could mediate human and DNN behaviour in the task (Zhan et al, 2019a;Yildirim et al, 2020). Our study thereby contributes to the debate of the degree to which convolutional DNNs can make use of shape information in images (Kubilius et al, 2016;Xu et al, 2018;Baker et al, 2018;Geirhos et al, 2019;Hermann & Kornblith, 2019;Doerig et al, 2020).…”
Section: Hypothesis-driven Research Using Generative Modelsmentioning
confidence: 91%
“…This meant simultaneously satisfying many functional requirements (Table 1), and multiple tasks ( Figure 5) instead of optimizing for a single query-dependent objective. It is an encouraging sign that many more recent models (Linsley et al, 2018;Kietzmann et al, 2019;Yildirim et al, 2020) have started incorporating insights from neuroscience toward building a unified general model for vision. We now consider the different properties of RCN from the viewpoint of triangulation strategy where we describe their neuroscience origins, their correspondence with the world, and their computational underpinnings.…”
Section: What Kind Of Visual Generative Model Is Suitable For Common mentioning
confidence: 98%